Laboratory diagnosis of von Willebrand disease - Patzke, J.; Schneppenheim, R. (Hämostaseologie, 2010)
Over the last decade, considerable progress has been made in the laboratory diagnosis of VWD. Precise, sensitive and automated VWF : Ag assays became widely available. The VWF : RCo performance was improved to a certain degree. However, the sensitivity, precision and general availability of automated applications is not yet optimal. Nevertheless, this type of assay is still recognized as superior to other activity assays, e. g. VWF : CBA assays and antibody-binding “activity” assays, for the detection of defects in VWF function.A decision limit of either 30 or 40 IU dl-1 VWF (VWF:RCo or VWF:Ag) is recommended for a diagnosis of type 1 VWD. Type 2 VWD can be differentiated from type 1 by calculating the VWF:RCo/VWF:Ag ratio.Improved and easier to perform multimer analysis and genetic testing are beginning to facilitate the diagnosis of the VWD type 1, 2A, 2B, 2N, 2M or 3. Within type 1 or 2, a decreased VWF survival can be detected by the VWFpp assay and its ratio to VWF : Ag.A new type of VWF activity assay, based on the binding of VWF to a GPIb〈-fragment, has been developed. One assay variant does not need ristocetin as a cofactor anymore. The performance investigations presented so far are very promising. It is probable that these GPIb〈-binding assays will detect functional VWF defects as the VWF : RCo assay, but are much more sensitive and precise. Fully automated applications on routine analyzers are expected to be commercialized soon.
Keywords: Von Willebrand disease; von Willebrand factor